Managing Revitalization to Conserve Cultural Heritage Kampong in Kauman Surakarta - Musyawaroh Musyawaroh; T.S. Pitana; M. Masykuri; Nandariyah Nandariyah (Institut Teknologi Sepuluh Nopember, 2017)
Kelurahan Kauman is one of the cultural heritage kampong in Surakarta, formerly inhabited by abdi dalem ulama Keraton and batik entrepreneurs. Kauman developed when Pakubuwono III built the Great Mosque in 1757, the kampong then developed into a batik industrial center in the early 1800s, shown by the number of luxury homes built by batik entrepreneurs that year. But in 1939 to 1970 batik companies went bankrupt; Therefore, the ancient houses and buildings were damaged and became a slum neighborhood. Revitalization of the area has been done since 2006, the economy rose again but the environmental conditions have not been optimal. The purpose of this study is to manage the revitalization program that has been done to find a better settlement strategy. The research was conducted by qualitative rationalistic approach. Data were collected through literature studies, interviews and field surveys. The sample selection is purposive, the sample being studied is the impact of revitalization on physical and non-physical environment and community activities of Kauman. Revitalization management is needed to make Kauman more comfortable in the future as a healthy settlement and can be developed into a tourist kampong to improve the welfare of the people who live in it